Cutaneous Plasmablastic Lymphoma in an Immunocompetent Patient with Long-Term Pyrimethamine Use for Essential Thrombocythemia: A Case Report and Literature Review - Ing Soo Tiong; Magreet Strauss; Michael B. Y. Lau; Shingirai Chiruka (Case Reports in Hematology)
We report a case of Epstein-Barr-virus-(EBV-) positive primary cutaneous plasmablastic lymphoma in a human-immunodeficiency-virus-(HIV-) negative, immunocompetent 62-year-old female patient. We postulate that her lymphoma development is due to the longstanding use of pyrimethamine for essential thrombocythemia. This has never been described in the literature.